The contribution of academic self-efficacy in predicting the goal orientations of adolescent girls in the Kasbah schools of AL Karak Governorate during the Corona pandemic - Alshamaileh, Roweida Ismail (Journal of Educational and Psychological Sciences, 2022)
This study aims to reveal the extent of The contribution of academic self-efficacy in predicting the goal orientations of adolescent girls during the Corona pandemic in the Kasbah schools of AL Karak Governorate, The study sample was formed of (104) female student was and their ages ranged from (13-16), And they were chosen by the simple random method, and two measures were developed: academic self-efficacy and targets designation, and their psychometric properties were verified. The results of the study concluded that there is an average level of academic self-efficacy and targets designation, and that there is a positive relationship between academic self-efficacy and targets designation, and that academic self-efficacy predicts targets designation by (60%).